Pharmacological Manipulation of DNA Methylation in Adult Female Rats Normalizes Behavioral Consequences of Early-Life Maltreatment - Keller, Samantha M.; Doherty, Tiffany S.; Roth, Tania L. (Frontiers in Behavioral Neuroscience, 2018)
Exposure to adversity early in development alters brain and behavioral trajectories. Data continue to accumulate that epigenetic mechanisms are a mediating factor between early-life adversity and adult behavioral phenotypes. Previous work from our laboratory has shown that female Long-Evans rats exposed to maltreatment during infancy display both aberrant forced swim behavior and patterns of brain DNA methylation in adulthood. Therefore, we examined the possibility of rescuing the aberrant forced swim behavior in maltreated-adult females by administering an epigenome-modifying drug (zebularine) at a dose previously shown to normalize DNA methylation. We found that zebularine normalized behavior in the forced swim test in maltreated females, such that they performed at the levels of controls (females that had been exposed to only nurturing care during infancy). These data help link DNA methylation to an adult phenotype in our maltreatment model, and more broadly provide additional evidence that non-targeted epigenetic manipulations can change behavior associated with early-life adversity.